Visualizing web server logs insights with elastic stack- a case study of ummail's access logs / Harni Yusnidar Muhammad and Jasni Mohamad Zain - Muhammad, Harni Yusnidar; Mohamad Zain, Jasni (Universiti Teknologi MARA Press (Penerbit UiTM), 2018)
One of the most significant information resources that often overlooked and it is mostly owned by the modern organization today is logs data. Likewise, logs data analytics is practised in many industries for different purposes, including website/system performance improvement, web development, information architecture, web-based campaigns/programs, network traffic monitoring, e-commerce optimization, marketing/advertising, etc. Many tools or approaches are available for this purpose, some are proprietary and some are open source. Studying the nature of these tools in finding the suitable and the right log analyzer in order to perform log analytics economically, efficiently and effectively will give advantages to the organization towards utilizing the primary source of information for identifying the system threats and problems that occur in the system at any time through Visualizing Insights of source using Elastic Stack. These kinds of threats and problems which existed in the system can be identified by analyzing the log file and finding the patterns for possible suspicious behaviour. A case study of UMMAIL's access logs is proposed to visualise web server logs. The system administrator's concern can then be furnished with an appropriate infographics representation regarding these security threats and problems in the system, which are generated after the log files, are analysed. Based on this signs the administrator can take appropriate actions.